Pengembangan Desa Wisata Kampung Kiyu Melalui Pemberdayaan Masyarakat Adat Dayak Meratus: Development of Kiyu Village as a Tourism Village through the Empowerment of Dayak Meratus Indigenous People - Utami, Suci; Maulana, Muhammad Rizky; Lestari, Lestari; Khalizah, Ainun; Rahmah, Shofa Aulia; Makmur, Makmur; Jaya, Frans Riano; Fernando, Zean; Nurullah, Aditya Fajar; Azizah, Khalifatul; Alhaidar, Muhammad Raffi; Anggraini, Siti Hana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The implementation of the community service and empowerment program initiated by Mapala Justitia Law Faculty Lambung Mangkurat University through PPK Ormawa 2023 was held in Kiyu Village, Hulu Sungai Tengah Regency, South Kalimantan. This area has excellent potential as a natural tourism destination, especially for climbing Mount Besar and Halau-Halau Peak. However, the tourism infrastructure in Kiyu Village is currently minimal. There is no post or basecamp for official registration of tourists, most of whom are climbers. Available accommodation is limited to a few guesthouses, which cannot support the increasing number of climbers. This program involves a team consisting of the Justitia Nature Lovers Student Organization (Mapala), Faculty of Law, Lambung Mangkurat University with activity supervisors who focus on developing the Kampung Kiyu Tourism Village in the Gunung Besar Conservation Area, Puncak Halau-Halau, part of the Meratus Geopark. The main activities of this program include The Great Mountain Climbing Post, Halau-Halau Peak, and Empowerment of the Dayak Meratus Indigenous People. The program aims to improve the development of local wisdom-based natural tourism villages and an effort to improve the economy of the local community. This program has a positive impact on the economy, infrastructure, environmental awareness, and promotion of Dayak Meratus's Indigenous cultural heritage with the achievement of this program in the form of the establishment of the mountain's basecamp building, publishing modules for the management of tourist villages, and socialization activities that have a positive impact implemented by local people.